Influencia de la ansiedad en los hábitos alimentarios de adultos mayores hipertensos de la microred Belén, Maynas – 2024 - Gordon Chasnamote, Kandy Raquel (2025)
The objective of this research was to determine whether anxiety influences the eating habits of hypertensive older adults who attend the different health centers that make up the Belén, Maynas – 2024 micro network. The research was quantitative, descriptive-comparative, cross-sectional, and correlational, involving a population of 500 older adults diagnosed with high blood pressure, of both sexes aged 60 to 75 years. The entire population was studied. The results regarding anxiety in the Belén Micro-Network showed that 88.8% have very low anxiety, 11.2% have moderate anxiety, and there was no severe anxiety, indicating that there is low anxiety among the surveyed individuals. Regarding eating habits in the Belén Micro-Network, it was found that 4.4% have healthy habits, 87.2% have habits leaning towards healthy, 8.4% have unhealthy habits, and there are no patterns of completely unhealthy habits. It is asserted that there is a custom of habits that tend towards healthiness. Analyzing the results of the relationship between the variables, with a Spearman's Rho value of 0.121 and a p-value of 0.007; it is concluded that there is a moderate positive correlation, and the general hypothesis is accepted: there is an influence of anxiety on the eating habits of elderly hypertensive adults who attend the different health centers that make up the Belén micro-network, Maynas – 2024.